Pengaruh Pembelajaran Online Terhadap Pemahaman Materi Mahasiswa Semester 4 Pada Mata Kuliah Keagenan Kapal di Politeknik Pelayaran Sumatera Barat - Salsabilla, Syafhana; Waruwu, Winda Mastiah; Kharisma, Alhafiz; Ezyoni, Muhammad Hasbi (Jurnal Cakrawala Bahari, 2024)
This study definitively examines how online learning affects the understanding of material of 4th semester students in the Ship Agency course at the West Sumatra Shipping Polytechnic. This study uses quantitative methods with non-parametric analysis. We collected data through questionnaires distributed to 57 4th semester students of the marine transportation study program and analyzed it using the Spearman correlation test. The results revealed a significant relationship between online learning and material understanding, with a correlation value of 0.654 and a significance level of 0.01. While online learning offers diverse ways to deliver information, network problems and limitations of direct interaction emerge as significant obstacles in the learning process. The results demonstrate that online learning enhances students' comprehension of the material. However, to make it more effective, improvements to the infrastructure and teaching techniques are still needed.